Meaning and Function of Local Wisdom in the Proverb (Limbaga) Simalungun - Asriaty R. Purba; Herlina Herlina; Jamorlan Siahaan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Aims to describe the meaning and function of local wisdom contained in proverbs or called limbaga Simalungun. The meaning and function of local wisdom is a general guideline or principle adopted by every member of society, especially in attitude and behavior, to meet social needs. Therefore, value is an idea related to what is considered good, worthy and desired by all levels of society in life. The data collection method used in this study is a descriptive qualitative method which tends to use analysis. The data collection methods used in this study are: library methods, observation methods and interview methods. The results of the analysis of this study indicate that the proverb (Limbaga) of Simalungun has a meaning and function of local wisdom.